Механізми екстрасудинного та внутрішньосудинного тромбоутворення: фундаментальні дослідження для потреб клінічної практики (за матеріалами наукового повідомлення на засіданні Президії НАН України 27 лютого 2019 р.) - Чернишенко, В.О. (Вісник НАН України, 2019)
Вивчення тонких механізмів молекулярних перетворень фібриногену під
час полімеризації дозволило виявити, що сполуки імуноглобулінової природи, поліпептиди та низькомолекулярний калікс[4]арен здатні специфічно
інгібувати формування фібринового каркасу тромбу. Такі сполуки можна розглядати як перспективні молекулярні платформи для створення
антитромботичних засобів, покликаних запобігати внутрішньосудинному тромбоутворенню, яке є причиною таких небезпечних патологій,
як інфаркт міокарда, ішемічний інсульт головного мозку тощо. На основі
розробок відділу структури та функції білка було створено також універсальний гемостатичний засіб «Карбогемостат», здатний ефективно стимулювати екстрасудинне тромбоутворення з метою запобігання
крововтраті при ушкодженнях кровоносних судин внаслідок різного роду
травм та під час хірургічних втручань. Haemostasis is the unique system of human organism that support blood flow in vessels and the termination of blood loss
after injury. The dynamic balance of haemostasis is provided by the interplay of several enzymatic systems that all are
targeted directly or indirectly on fibrinogen. Fibrinogen is soluble protein of blood that when activated by thrombin
converts to fibrin that is able to form polymeric fibrin which is the core of thrombus. To study the structure and functions
of fibrin several molecular instruments are used, among them are monoclonal antibodies, synthetic peptides, lowmolecular
weight compounds and specific proteases.
Monoclonal antibody I-5А specific to fibrinogen fragment Аα509-610 is shown to be an effective inhibitor of lateral
association of protofibrils during fibrin polymerization. Thus we assume the presence of some previously unknown site of
lateral association of protofibrils within the αC-region of molecule. Also inhibitory antibody I-5А or its recombinant
single chain analogue (scFv) can be assumed as the prospective agent for the inhibition of thrombus formation in vivo.
We also found the residues of fibrinogen molecule that participate in both stages of fibrin polymerization process: Aα-
91-103, Bβ-125-135 and γ-69-77. The synthetic peptides that mimic these residues together or separately can be used for
prevention of thrombus formation.
Finally, unique calix[4]arene C-145 with strong antithrombotic activity is found. We demonstrate that C-145 directly
blocked A:a knob-hole interactions during fibrin polymerization thus preventing the formation of three-dimensional
fibrin network that is the core of thrombus. Such unique properties allow assuming the possible use of C-145 in
antithrombotic therapy. In vivo studies demonstrated that C-145 being introduced to laboratory mice per orally acts as
effective anticoagulant agent.
Apart of the prevention of intravascular coagulation we also focus on the initiation of extravascular clotting that is
one of the crucial points for the prevention of blood loss after traumas or in surgery. Direct comparison in the model of
massive blood loss demonstrated that developed haemostatic agent was more effective for blood loss prevention then
commercially available Celox (UK).